2016
DOI: 10.1007/s12033-016-9945-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of Glucaric Acid from Hemicellulose Substrate by Rosettasome Enzyme Assemblies

Abstract: Hemicellulose biomass is a complex polymer with many different chemical constituents that can be utilized as industrial feedstocks. These molecules can be released from the polymer and transformed into value-added chemicals through multistep enzymatic pathways. Some bacteria produce cellulosomes which are assemblies composed of lignocellulolytic enzymes tethered to a large protein scaffold. Rosettasomes are artificial engineered ring scaffolds designed to mimic the bacterial cellulosome. Both cellulosomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The conversion yield was not reported by Lee et al [15], who proposed the in vitro pathway with three enzymes including endo-xylanase, α-glucuronidase, and uronate dehydrogenase to produce (methyl)glucaric acid from birchwood xylan. The authors reported a maximum production of 0.7 mM (methyl)glucaric acid from 1% birchwood xylan after more than 2 h, as quantified by NADH absorbance at 340 nm [15]. Provided that a similar xylan source was used, this would be equivalent to a conversion yield of ~ 20%.…”
Section: Oxidation Of 4-o-methyl D-glucuronic Acid By Goox Variantsmentioning
confidence: 78%
See 2 more Smart Citations
“…The conversion yield was not reported by Lee et al [15], who proposed the in vitro pathway with three enzymes including endo-xylanase, α-glucuronidase, and uronate dehydrogenase to produce (methyl)glucaric acid from birchwood xylan. The authors reported a maximum production of 0.7 mM (methyl)glucaric acid from 1% birchwood xylan after more than 2 h, as quantified by NADH absorbance at 340 nm [15]. Provided that a similar xylan source was used, this would be equivalent to a conversion yield of ~ 20%.…”
Section: Oxidation Of 4-o-methyl D-glucuronic Acid By Goox Variantsmentioning
confidence: 78%
“…Furthermore, fermentation approaches can complicate product recovery, due to the presence of medium components and other metabolites/intermediates. A cell-free approach to produce 4-O-methyl d-glucaric acid (or methyl glucaric acid, for short) from glucuronoxylan was reported [15], where three enzymes including an endo-xylanase (EC 3.2.1.8), α-glucuronidase (EC 3.2.1.139), and uronate dehydrogenase (EC 1.1.1.203) were used in a cocktail or co-localized on a scaffold. The xylanase cleaved glucuronoxylan to various xylo-oligosaccharides, of which some contained MeGlcA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 a). The pathway was different from the previously reported pathway constructed in recombinant E. coli , and used three enzymes: xylanase (Xyn) from Flavobacterium sp., glcuronidase (AG) from a rumen metagenomic library, and Udh from P. mendocina [ 67 ]. These three enzymes were co-localized into a scaffold and the final product GA increased by 20% compared with the case when the three enzymes were free in solution.…”
Section: Cell-free Multi-enzyme Catalysis Approaches To Produce Gamentioning
confidence: 99%
“…
Fig. 4 In vitro cascade for production of GA. Four different methods of synthesizing GA in vitro are represented by different colored text and arrows [ 64 , 67 69 ]. a Pink text indicates the GA synthesis route starting from sucrose.
…”
Section: Cell-free Multi-enzyme Catalysis Approaches To Produce Gamentioning
confidence: 99%